2016
DOI: 10.1016/j.cmet.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Never Waste a Good Crisis: Confronting Reproducibility in Translational Research

Abstract: The lack of reproducibility of preclinical experimentation has implications for sustaining trust in and ensuring the viability and funding of the academic research enterprise. Here I identify problematic behaviors and practices and suggest solutions to enhance reproducibility in translational research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 79 publications
0
85
0
Order By: Relevance
“…The improvement of the value of biomarker research, as well as strategies to avoid poor reproducibility of results, is an ongoing debate in medical sciences and beyond (23)(24)(25). The unwitting inclusion of serum and plasma samples of insufficient quality may contribute to poor reproducibility and misleading findings in biomarker studies, but currently no objective and reliable assessment of sample quality is generally used in medical research (except the identification and exclusion of hemolytic samples).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of the value of biomarker research, as well as strategies to avoid poor reproducibility of results, is an ongoing debate in medical sciences and beyond (23)(24)(25). The unwitting inclusion of serum and plasma samples of insufficient quality may contribute to poor reproducibility and misleading findings in biomarker studies, but currently no objective and reliable assessment of sample quality is generally used in medical research (except the identification and exclusion of hemolytic samples).…”
Section: Discussionmentioning
confidence: 99%
“…The poor reproducibility of biomarker and other research studies is a point that is currently being intensely debated (23)(24)(25), and the temperature and time to processing of blood is one of several preanalytical variables that can lead either to samples being outliers or to large scatter in metabolite measurements. In general, the sample collection procedures used in biomarker and other studies, although tightly controlled by protocols and SOPs, are heterogeneous with respect to logistical, personnel-related, and organizational conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, histological studies reported GLP-1R expression within pancreatic ducts and preneoplastic lesions in animals and humans, and preclinical experiments linked incretin signaling to pancreatic inflammation and cell proliferation in rodents (74). Notably, efforts to reproduce many of these preclinical findings were unsuccessful, reflecting limitations of many of the reagents and experimental designs used in these studies (74,75). Subsequent examination of a large number of pancreata from different strains of rats revealed spontaneous rates of histological abnormalities, including pancreatitis, in up to 72% of animals never exposed to incretin therapy (76).…”
Section: Adverse Events Associated With Glp-1r Agonistsmentioning
confidence: 99%
“…Although sensitive and specific methods are available for cellular and tissue localization of GLP-1R mRNA and protein (Fig. 2), the literature is replete with examples of failure to apply rigorous methodology for detection of GLP-1R expression, leading to erroneous conclusions surrounding the mechanisms of GLP-1 action (75). For example, the observation of numerically greater retinopathy events in calls into question the putative localization and functional importance of GLP-1R expression in the retina versus the established importance of rapid glucose lowering, which predisposes toward development of retinopathy.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…The Crisis of Reproducibility has been the subject of many editorials with a series of proposed explanations [1, [6][7][8][9][10], with some even questions whether it is a "real crisis" [11]. The vast majority of these opinions fall into two categories:…”
Section: Introductionmentioning
confidence: 99%